2017
DOI: 10.1111/are.13439
|View full text |Cite
|
Sign up to set email alerts
|

Depletion study and estimation of withdrawal periods for florfenicol and florfenicol amine in pacu (Piaractus mesopotamicus)

Abstract: The intensive production of farmed fish is at a global all-time high, and the control of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Based on this information, we analysed the residues of antibiotics in fish muscles as an edible tissue obtained in the current literature to understand the possible human health risk resulting from direct consumption of fish treated with antibiotics used in global aquaculture (Table 8). We found that, the residues of most studied antibiotics detected in muscles from various fish species during different sampling periods were higher than MRLs established for most antibiotics such as OTC Malvisi et al 1996;Namdari et al 1996;Namdari et al 1998;Meinertz et al 2001;Bebak-Williams et al 2002;Rigos et al 2002;Bernardy et al 2003;Chen et al 2004;Zhang & Li 2007;Romero Gonz alez et al 2010;Paschoal et al 2012;Elia et al 2014;Limbu et al 2018;Rosa et al 2019;Vorbach et al 2019), FFC (Wrzesinski et al 2006;Feng et al 2008;Lim et al 2010;Di Salvo et al 2013;Meinertz et al 2014;Gaikowski et al 2015;Marques et al 2018), TMP (Phu et al 2015;Zonaras et al 2016;Rosa et al 2019), SMZ (Phu et al 2015;Limbu et al 2018), sulfamethazine (Nunes et al 2018), sulfadiazine (Romero Gonz alez et al 2010;Zonaras et al 2016;Rosa et al 2019), FMQ (Tyrpenou et al 2003), ENRO (Intorre et al 2000;Xu et al 2006), CPF (Xu et al 200...…”
Section: Potential Human Health Risk Via Fish Consumptionmentioning
confidence: 77%
See 1 more Smart Citation
“…Based on this information, we analysed the residues of antibiotics in fish muscles as an edible tissue obtained in the current literature to understand the possible human health risk resulting from direct consumption of fish treated with antibiotics used in global aquaculture (Table 8). We found that, the residues of most studied antibiotics detected in muscles from various fish species during different sampling periods were higher than MRLs established for most antibiotics such as OTC Malvisi et al 1996;Namdari et al 1996;Namdari et al 1998;Meinertz et al 2001;Bebak-Williams et al 2002;Rigos et al 2002;Bernardy et al 2003;Chen et al 2004;Zhang & Li 2007;Romero Gonz alez et al 2010;Paschoal et al 2012;Elia et al 2014;Limbu et al 2018;Rosa et al 2019;Vorbach et al 2019), FFC (Wrzesinski et al 2006;Feng et al 2008;Lim et al 2010;Di Salvo et al 2013;Meinertz et al 2014;Gaikowski et al 2015;Marques et al 2018), TMP (Phu et al 2015;Zonaras et al 2016;Rosa et al 2019), SMZ (Phu et al 2015;Limbu et al 2018), sulfamethazine (Nunes et al 2018), sulfadiazine (Romero Gonz alez et al 2010;Zonaras et al 2016;Rosa et al 2019), FMQ (Tyrpenou et al 2003), ENRO (Intorre et al 2000;Xu et al 2006), CPF (Xu et al 200...…”
Section: Potential Human Health Risk Via Fish Consumptionmentioning
confidence: 77%
“…2010; Marques et al . 2018). As such, analysing human health risk of the parent antibiotic by considering withdrawal periods may underestimate the risk.…”
Section: Potential Human Health Risk Via Fish Consumptionmentioning
confidence: 99%
“…They also reported that the 500°C‐day time was much greater than necessary. Marques, Paschoal, Barone, Cyrino, and Rath () determined WT value for the sum of FF and FFA in natural proportions of juvenile pacu ( Piaractus mesopotamicus ) that were fed 10 consecutive days with a diet containing FF (10 mg/kg bw) to be 5 days (water temperature 25.8°C) or 129 degree days. In another study, FFA was analysed from fillet tissue of rainbow trout treated with FF‐medicated feed at 20 mg/kg bw/day for 10 days (water temperatures of ∼13 ◦ C).…”
Section: Discussionmentioning
confidence: 99%
“…At present, there are many reported methods for detecting TAP, FF and FFA residues, including methods based on high-performance liquid chromatography (HPLC) [14,15,16], gas chromatography (GC) [17,18], liquid chromatography-tandem mass spectrometry (LC-MS/MS) [19,20,21,22], and gas chromatography-tandem mass spectrometry (GC-MS) [23,24]. When using GC to analyze CAP drug residues, the target needs to be derivatized, making the analysis process cumbersome.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, developing a simple, fast and low-cost analytical method that meets the detection requirements is of great importance. Moreover, in the reported detection methods, the sample matrices used for analysis were generally animal tissues [15,26] or aquatic products [21,27], and there are few reports on detection methods for poultry eggs [14]. Xie et al [14] established an HPLC-FLD method for the determination of TAP, FF and FFA residues in eggs and sample pretreatment using a liquid-liquid extraction method, ethyl acetate:acetonitrile:ammonium hydroxide (49:49:2, v/v/v ) as an extractant, delipided in n-hexane.…”
Section: Introductionmentioning
confidence: 99%